Administration of Schools using the Principles of Good Governance of School Administrators, under the Office of Phatthalung Primary Educational Service Area 1 - ทองชู ปรียานุช; ศิริสุข กนกกร (Al-HIKMAH Journal, 2023)
This study examined the administration of schools using the principles of good governance of school administrators, under the office of Phatthalung Primary Educational Service Area 1. The objectives were to: 1) study of administration of schools using the principles of good governance of school administrators, under the office of Phatthalung Primary Educational Service Area 1., 2) compare the administration of schools by using the principles of good governance of school administrators, under the office of Phatthalung Primary Educational Service Area 1; which were classified by educational degree, work experience, and school size., and 3) gather the recommendations for administration of schools by using the principles of good governance of school administrators, under the office of Phatthalung Primary Educational Service Area 1. The samples used in this study were 272 teachers under the office of Phatthalung Primary Educational Service Area 1. They were obtained by stratified random sampling according to the size of the schools and were randomly selected by simple random sampling or drawing lots by lottery. The tool used in this study was a 5-level Rating Scale. The statistics used were frequency, percentage, mean, standard deviation, t-test differential test, and One-way ANOVA. The results showed that: 1) Overall and each aspects of administration of schools using the principles of good governance of school administrators, under the office of Phatthalung Primary Educational Service Area 1; were at a high level. 2) Teachers under the Office of Phatthalung Primary Educational Service Area 1 with different educational degree, work experiences, and school sizes, were no differences in opinions about the administration of schools using the good governance of the school administrators, in both overall and each aspects. 3) The first three recommendations aspects for administration of schools using the principles of good governance of school administrators, under the office of Phatthalung Primary Educational Service Area 1 were: Moral principles, Principle of value for money, and Principle of participation, respectively.